Agricultura irrigada, meio ambiente e intervenções públicas no território do alto sertão sergipano - Santos, Genésio José dos (2011)
From the theme "Irrigated Agriculture, Environment and Public Interventions in the High Wilderness Territory Sergipe", aimed to analyze from categories such as geographical territory, space and landscape from the conditions of public assistance projects in California, New California Gator Curituba and, with respect to their agriculture, their environment and quality of life of its population. In the construction of this thesis, it is recognized that as they are discussed the questions posed, its relevance is related to the endless search for proposals to support the actions of the government and also to the people directly involved in this context, towards the acquisition of an effective quality of life. The theme of this work is in tune with reality arising from the new territorial configuration it requires and creates new landscapes and even new behaviors arising from a new form of governance, where actors are closer to the grassroots organizations and the decisions, although manipulated at some times and in some sectors are more collectivized. To reach conclusions plausible and consistent with the goals we used the empirical-analytical method, following methodological steps typical of that method. With the raid made on the theoretical principles established and pursuing the goals set, one reaches the conclusion that public intervention in the High Wilderness Sergipe, especially in the cities of San Francisco Canindé and Poço Redondo, creates a new territorial configuration, landscape and spatial mainly in its agriculture and California Project, California and New Gator Curituba are the most striking examples of this action. We also conclude that even with this intervention the situation of poverty among its population remains rural and the Poço Redondo reflects this condition more explicitly. But the High Wilderness Territory Sergipano now presented a new dynamic, especially in the last quarter-century. Showed an increase in the volume of goods produced and also the services produced. He also presented a considerable growth of established structures in rural and urban projects such as irrigated agriculture, with areas in constant growth, in contrast with the expansion of poverty of its population.